Exploring the prevalence and characteristics of adverse drug events among older adults in South Korea using a national health insurance database - Choi, Eunkyeong; Kim, Siin; Suh, Hae Sun (Frontiers in Pharmacology, 2022)
Adverse drug events (ADEs) in the elderly frequently occur because of their multiple chronic diseases and complexity of drug therapy. To better understand ADEs, the prevalence and characteristics of ADEs in elderly South Korean patients were assessed. The National Health Insurance databases for 2015 and 2016 were used for the analysis. We included patients aged ≥ 65 years that had at least one claim with the diagnosis codes ‘drug-induced,’ ‘poisoning by drug,’ and ‘vaccine-associated’ each year for the base-case analysis. To minimize the underestimation of ADE prevalence, we also used an extended definition analysis by adding the ‘ADE very likely’ codes. We estimated the prevalence of ADEs by sex, age group, and type of insurance and examined the frequent types of ADEs in 2015 and 2016. In the base-case analysis, ADE prevalence in individuals aged 65 years and older was 27.48 per 1,000 persons in 2015 and 27.72 per 1,000 persons in 2016. With advanced age, the prevalence of ADE tended to increase, peaking in the age group of 75–79 years. In addition, the ADE prevalence was higher in females and Medical Aid enrollees. The most frequently occurring ADE was ‘allergy, unspecified,’ followed by ‘other drug-induced secondary parkinsonism’, and ‘generalized skin eruption due to drugs and medicaments.’ When we examined the extended definition analysis, the prevalence of ADEs was 44.72 per 1,000 persons in 2015 and 45.19 per 1,000 persons in 2016, which significantly increased from those estimated in the base-case analysis. Among the older adults, the prevalence of ADE was higher in advanced age, females, and Medical Aid enrollees. In particular, allergy and drug-induced secondary parkinsonism frequently occurred. This study provides evidence that health policies addressing the prevention and management of ADEs should be a priority for the most vulnerable elderly patients.